Information and competition entry - Mara Ewers (Institute for the Study of Labor (IZA), 2012)
This paper studies the influence of information on entry choices in a competition with a controlled laboratory experiment. We investigate whether information provision attracts mainly high productivity individuals and reduces competition failure, where competition failure occurs when a subject loses the competition because the opponent holds a higher productivity. Information on the opponent is a promising nudge to raise individuals' awareness towards the complexity of the decision problem and to update beliefs about success. In the experiment, subjects face the choice between a competition game and a safe outside option. We analyze subjects' entry behavior with a benchmark treatment without information and three treatments, where we exogenously manipulate the information on the opponents. Our results are, (1) information on the productivity distribution of all potential opponents reduces competition failures by more than 50%, (2) information on the distribution is sufficient, i.e. precise information on the matched opponent's type does not further diminish failure rates.
urn:nbn:de:101:1-201206147063
Keywords: C91; D03; D61; D81; D82; M13; M51; 330; competition; experiment; information; overconfidence; self-assessment; self-selection; tournament; Extensives Spiel; Wettbewerb; Markteintritt; Information; Produktivität; Test